(untitled) (International Journal of Innovative Technologies in Economy, 2018)
This article examines the distribution of taxes between the budgets of the budget system to ensure fiscal balances in Uzbekistan. In identifying existing problems were developed suggestions and recommendations with regard to prospects for fiscal balances based on international best practices.